Biochemical, morphological and cytochemical studies of enhanced autolysis of Saccharomyces cerevisiae. 2. Morphological and cytochemical studies - Kollár, R; Vorísek, J; Sturdík, E (Folia microbiologica, 1993)
Morphological and cytochemical observation of Saccharomyces cerevisiae undergoing of induced autolysis were done in response to various chemical inducers of autolysis (NaCl, ethanol, fresh autolyzate). Changes in the inner structure of yeast cells were monitored by transmission electron microscopy and the surface of the cell wall was observed by scanning electron microscopy during autolysis. Cytochemical characterization of autolyzed cells was performed using four synthetic substrates for determination of proteinase activities but only carboxypeptidase Y could be detected in the vacuolar membranes. The morphological studies supported the data obtained from biochemical studies and confirmed that optimized conditions of autolysis have a significant effect on the structural changes of autolyzed yeast.
Keywords: chlorid sodný; Histocytochemistry; intracelulární membrány; elektronová mikroskopie; histocytochemie; Microscopy, Electron, Scanning; Intracellular Membranes; ethanol; mikroskopie elektronová rastrovací; Ethanol; karboxypeptidasy; endopeptidasy; kathepsin A; Microscopy, Electron; Vacuoles; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae; Cathepsin A; Endopeptidases; autolýza; Carboxypeptidases; Autolysis; Sodium Chloride; vakuoly; Saccharomyces cerevisiae Proteins